Anesthetic Management Using Epidural Analgesia for Emergency Laparoscopic Cholecystectomy in a Patient with Lupus Anticoagulant Positivity and Prolonged Activated Partial Thromboplastin Time - Yasuhiro Watanabe; Toru Kaneda (Case Reports in Anesthesiology)
Lupus anticoagulant (LA), an antiphospholipid antibody, prolongs in vitro activated partial thromboplastin time (APTT) despite the presence of a hypercoagulable state in vivo. Irrespective of whether they receive antithrombotic therapy, meticulous anesthetic management is imperative in patients with LA positivity to prevent thrombotic complication. Additionally, emergency surgery in such patients can be challenging, as the time to devise perioperative strategies is limited. Here, we described the case of a patient with LA positivity and prolonged APTT who underwent emergency laparoscopic cholecystectomy with successful anesthetic management using epidural analgesia. An 83-year-old woman presented with acute cholecystitis and underwent emergency laparoscopic cholecystectomy. Preoperative blood test results revealed a prolonged APTT of 83 s, prothrombin time/international normalized ratio of 1.14, and normal platelet count. The patient had experienced a marked prolongation of APTT ten years previously, which was attributed to LA positivity, and she had previously undergone surgery for rectal cancer under general and epidural anesthesia. The patient did not receive antithrombotic therapy, and she demonstrated neither liver dysfunction nor a bleeding tendency. We prioritized optimal analgesia to enable early mobilization; therefore, an epidural catheter was placed in preparation for transition to open abdominal surgery. The operation was completed under laparoscopy, and good pain control was achieved postoperatively with continuous epidural analgesia, facilitating early ambulation. The epidural catheter was removed on the second postoperative day, and the patient did not develop any signs of thromboembolism or neurologic complications during her hospital stay. Anesthetic management for emergency laparoscopic cholecystectomy was successfully performed using epidural analgesia in a patient with LA positivity and prolonged APTT. Careful evaluation of laboratory data, treatment history, and clinical symptoms is of critical importance in such patients.